2010
DOI: 10.1002/chp.20071
|View full text |Cite
|
Sign up to set email alerts
|

Electronic communities of practice: Guidelines from a project

Abstract: The timely incorporation of health research into the routine practice of individual health practitioners and interprofessional teams is a widely recognized and ongoing challenge. Health professional engagement and learning is an important cog in the wheel of knowledge translation; passive dissemination of evidence through journals and clinical practice guidelines is inadequate when used alone as an intervention to change the practices of the health professionals.An evolving body of research suggests that commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 37 publications
1
54
0
1
Order By: Relevance
“…CoP have been studied in human resource development (Jorgensen & Keller, 2008); industry (Fuller, Hodkinson, Hodkinson, & Unwin, 2005) and teacher education (Yandell & Turvey, 2007); and in recent years, in health quality improvement (White, Suter, Parboosingh, & Taylor, 2008) and continuing professional development (Ho et al, 2010;Parboosingh, 2002). CoP, however, have been criticised for being over-simplistic (Edwards, Daniels, Gallagher, Leadbetter, & Warmington, 2009) and lacking sound theoretical grounds (Sorberg-Walker, 2008).…”
Section: Workplace Learning Theoretical Frameworkmentioning
confidence: 99%
“…CoP have been studied in human resource development (Jorgensen & Keller, 2008); industry (Fuller, Hodkinson, Hodkinson, & Unwin, 2005) and teacher education (Yandell & Turvey, 2007); and in recent years, in health quality improvement (White, Suter, Parboosingh, & Taylor, 2008) and continuing professional development (Ho et al, 2010;Parboosingh, 2002). CoP, however, have been criticised for being over-simplistic (Edwards, Daniels, Gallagher, Leadbetter, & Warmington, 2009) and lacking sound theoretical grounds (Sorberg-Walker, 2008).…”
Section: Workplace Learning Theoretical Frameworkmentioning
confidence: 99%
“…Due to the scope and focus of this paper, we limit our analysis to one of these theories as it applies to the tertiary healthcare setting: communities of practice theory. This theory addresses interprofessional cultural competencies by encouraging healthcare professionals to work collaboratively through building social identity and sharing knowledge (Ho et al, 2010). When selecting a model for implementation, continuing IPE educators should consider how other theories such as Lave and Wenger's (1991) ''communities of practice'' learning theory might (or might not) be received in their context.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because online learning might not require facilitators. In contrast, a recent online IPE study using communities of practice framework showed that facilitators were necessary to ensure sustainability of the program as health professionals needed regular guidance in developing effective teamwork skills (Ho et al, 2010). Although the W(e) Learn model meets the needs of continuous IPE in the tertiary care setting, it has only been tested in a long term care environment.…”
Section: Concluding Commentsmentioning
confidence: 94%
“…Participants in a community of practice must exercise ownership of the KE process and feel they can self-organize for the interaction and community to be successful over time (Demiris, 2006;Ho et al, 2010). We therefore elected to implement the wiki as a longer-term sustainability strategy.…”
Section: Discussionmentioning
confidence: 99%